PENGARUH PENGAMBILAN KEPUTUSAN DALAM BERBELANJA ONLINE SHOP DI KOTA MEDAN - fasya, fasya (IAIN Langsa, 2018)
This study aims to determine how much influence the variable direct and indirect advertising, product quality, price and the level of confidence in the purchasing decisions through an online shop in the city of Medan. The method used in this study is quantitative approach using path analysis with multiple linear regression model is supported by test models and statistical tests using SPSS version 17. Findings from the research showed structural model 1 in unison that approximately 72.1% of advertising variables , product quality, the level of trust and influence purchasing decisions through an online shop in the city of Medan, while 27.9% is explained by other factors. In two simultaneous structural model that approximately 56.6% variable advertising, product quality and prices affect the level of trust while 43.4% is explained by other factors. The test results show the significance of the indirect impacts their indirect effect of the variable quality of the products on purchase decisions online through a confidence level significantly.